Farbe - Macht - Körper : Kritische Weißseinsforschung in der europäischen Kunstgeschichte - Greve, Anna (KIT Scientific Publishing, 2013)
From the 16th century to the 18th century skin colors have been stereotyped and stylized as essential characteristics of race. Color is of vital importance for artistic constructions of the body. This publication examines to what extent art has prepared the racist discourse by visual means and thus exercises structural violence. It is shown that the materialization of imaginary images contributes to the construction of difference in artworks.